Vulnerability assessment of Iran's rural-farmer households during COVID-19 pandemic - Shokati Amghani, Mohammad; Savari, Moslem; Choobchian, Shahla (Frontiers in Public Health, 2022)
The COVID-19 pandemic caused an emergency around the world, especially in rural communities, and imposed great disasters on human societies, so it's devastating effects on mental health indicators, economy, environment, and social relations are known to everyone. But the accurate assessment of its damage to human societies can help to manage this phenomenon during and post-COVID-19 pandemic. To that end, the present study was conducted for vulnerability assessment of wheat farmers to the COVID-19 pandemic in northwest Iran. The main data collection tool in this study was a questionnaire that was designed based on the Me-bar model, but for the accurate vulnerability assessment, new parameters were added based on the theoretical research literature and the COVID-19 pandemic. The sample size was selected from 420 wheat farmers living in East Azerbaijan Province, the northwest of Iran, using the Kerjcie and Morgan's table. The results showed that for economic vulnerability, the rural poverty was the most important cause of vulnerability of the studied rural households and access to information was most important cause of social vulnerability. Also, the results showed that for psychological vulnerability, the self-efficacy was the most important cause of vulnerability. In other results, irrigation parameters of agricultural lands were the most important cause of environmental vulnerability. The study results showed that the studied farmers have experienced high levels of vulnerability and were strongly affected by economic, social, psychological, and environmental damages. Moreover, the results showed that the farmers of Shabestar and Maragheh had the highest level of vulnerability. In general, the study results can provide policymakers with new insights into the field of COVID-19 pandemic management because the vulnerability of farmers has been identified using 39 parameters.